2012
DOI: 10.1021/jf300490w
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of Interfacial Proteins in Oil-in-Water Emulsions Prior to and During Lipid Oxidation

Abstract: Lipid oxidation is a major cause for the degradation of biological systems and foods, but the intricate relationship between lipid oxidation and protein modifications in these complex multiphase systems remains unclear. The objective of this work was to have a spatial and temporal insight of the modifications undergone by the interfacial or the unadsorbed proteins in oil-in-water emulsions during lipid oxidation. Tryptophan fluorescence and oxygen uptake were monitored simultaneously during incubation in diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 51 publications
9
42
0
Order By: Relevance
“…Fluorescence peak maxima were found at emission wavelengths around 345 nm in adsorbed proteins and around 332 nm in unadsorbed proteins. The difference in peak maxima wavelengths was also reported previously (Berton, Ropers, Guibert, Solé, & Genot, ; Salminen, Heinonen, & Decker, ) and is due to the conformational differences in the proteins from aqueous and cream phase and the location of tryptophan in these structures (Munishkina & Fink, ). Oxidative degradation of interfacial proteins in MWT emulsions was more advanced compared to CTT emulsions (40% decrease in Trp fluorescence vs. 30% from day 1 in CTT) most likely due to more advanced propagation of lipid oxidation in MWT emulsions (Figure ).…”
Section: Resultssupporting
confidence: 83%
“…Fluorescence peak maxima were found at emission wavelengths around 345 nm in adsorbed proteins and around 332 nm in unadsorbed proteins. The difference in peak maxima wavelengths was also reported previously (Berton, Ropers, Guibert, Solé, & Genot, ; Salminen, Heinonen, & Decker, ) and is due to the conformational differences in the proteins from aqueous and cream phase and the location of tryptophan in these structures (Munishkina & Fink, ). Oxidative degradation of interfacial proteins in MWT emulsions was more advanced compared to CTT emulsions (40% decrease in Trp fluorescence vs. 30% from day 1 in CTT) most likely due to more advanced propagation of lipid oxidation in MWT emulsions (Figure ).…”
Section: Resultssupporting
confidence: 83%
“…5). This is in line with results previously reported by Berton et al (2012) who found the highest carbonyl concentrations at the lowest protein solubilities in the creamed phase of an emulsion.…”
Section: Carbonyl Formation During Aqueous Fractionationsupporting
confidence: 93%
“…The carbonyl concentration is in fact underestimated because less than half of the total protein amount was solubilized in the guanidine solution. However, the LPIs at pH 4.5 and pH 7 have the highest solubility in the guanidine solution and the lowest carbonyl concentrations, which concurs with the behaviour of the unabsorbed proteins found in the aqueous phase of an emulsion (Berton et al, 2012). This thereby suggests that AF is a suitable process to obtain chemically (oxidatively) stable LPIs.…”
Section: Carbonyl Formation During Aqueous Fractionationsupporting
confidence: 70%
See 1 more Smart Citation
“…2,3 In O/W emulsions, proteins can typically be adsorbed at the interface surrounding the oil droplets and/or be present in the aqueous phase. 1,4 Therefore, the location of the proteins and their respective concentrations in one or the other phase needs to be taken into account when the interaction between food proteins and free reactive aldehydes and other lipid oxidation products in emulsions are studied.…”
Section: ■ Introductionmentioning
confidence: 99%